2009
DOI: 10.1007/s00127-009-0051-3
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of case managers’ expressed emotion to clients’ outcomes

Abstract: Family psychoeducation interventions, an evidence-based practice, have been demonstrated to be effective in reducing relapse of relatives with serious mental illness. Given the clinical evidence that EE is modifiable, it is expected that such educational training for non-familial caregivers will have the same potential as for family caregivers. Providers dealing with challenging clients may also need support and skills to better handle difficult situations, especially direct support providers like case manager… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…For example, it has been noted that EE research has been a strong impetus in the creation of both family therapies and hospital-staff interventions that focus on the role EE plays in interacting with persons with psychopathological problems [33, 34]. While some studies have demonstrated that high EE is related to the negative illness perceptions of caretakers toward their patients [11], not all studies have been able to replicate these findings [35].…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been noted that EE research has been a strong impetus in the creation of both family therapies and hospital-staff interventions that focus on the role EE plays in interacting with persons with psychopathological problems [33, 34]. While some studies have demonstrated that high EE is related to the negative illness perceptions of caretakers toward their patients [11], not all studies have been able to replicate these findings [35].…”
Section: Discussionmentioning
confidence: 99%
“…(4) There is high incidence of inappropriate communication stereotypes in the families, leading to increased expression of emotion (expressed emotion). Expressed emotion (EE) has been studied in families of a relative with schizophrenia as well as other psychiatric disorders; and high EE (hostile, critical, and over involved) families have been found to be strongly related to relapse 24 . When the families in this sudy were divided into two groups, families with high EE and those with low EE, it was found that discharged patients returning to a high EE family had a 3-4-fold higher risk of relapse than patients who returned to a low EE family 86 .…”
Section: The Psychoeducational Program At the Department Of Psychiatrmentioning
confidence: 99%
“…Further, the difficulty in engaging patients and their carers during PEP has made the outcomes of the programs inconclusive [21][22][23] . In the United States, family psychoeducation interventions are currently considered one of five evidence-based psychosocial interventions for persons with severe mental illness, particularly those with schizophrenia 24 . As many as 65% of discharged psychiatric patients return to live with a family member 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Health care providers' attitudes towards psychosis play a key role in access to services and client prognosis. Research supports the hypothesized role of provider attitudes in mediating the relationship between therapeutic alliance and outcomes (Solomon et al, 1995(Solomon et al, , 2010Fenton et al, 1997;Sartorius, 2002). Similarly, practitioner behaviors also moderate client outcomes, beyond the effect of their attitudes towards psychosis.…”
Section: Introductionmentioning
confidence: 85%